E crew management system for Malaysia airlines (ACMS) based on web application using three-tier architecture - Sukhdev Singh, Darsan Singh (2014)
Airline Crew Management System is developed for the purposes of managing the cabin crew in Malaysia Airlines. This system gives the ability to the Management to manage their crew wisely. This new system makes the management to overcome their current problem in the current system and provides best service towards to achieve a good standard in crew management. The system is developed according to the user's requirement that was obtained through an early research done before developing this system. Airline Crew Management System is user friendly, straight forward and clear where it is easy for all cabin crew to use it, even with less computer knowledge. As for the methodology of this system, Evolutionary Prototype Model was selected. This gives an easier development process to the developer. Other than that, Three-Tier architecture was implemented in this system design. Unified Modeling Language (UML) definitely gave the developer a clearer picture of the system designing. PUP and java script was selected as a programming language and MySQL server is selected as the database administrator. Basically, Airline Crew Management System was developed to manage all the cabin crew in Malaysia Airlines efficiently and systematically.